A norm about harvest division is maintained by a desire to follow tradition, not by social policing - Minhua Yan; Zhizhong Li; Yuanmei Li; Robert Boyd; Sarah Mathew (Proceedings of the National Academy of Sciences, 2025)
Determining how people behave in contexts governed by social norms can clarify both how norms influence human behavior and how norms evolve. We examined cooperative farming harvest division among the Derung, a Tibeto-Burman-speaking horticultural society in southwestern China. In the village of Dizhengdang, the norm dictates that cofarming harvests should be divided equally among participating households. This contrasts with an alternative norm followed in some other Derung villages that holds that harvests should be divided equally among participating laborers. Rational choice theory and evolutionary models of norm-based cooperation assume that individuals weigh the material and social payoffs of different actions and follow norms because doing so maximizes their payoff. However, the behavior of the Derung in Dizhengdang is not consistent with payoff maximization. Using interviews on co-farming behaviors and attitudes, along with an ultimatum game experiment framed as co-farming harvest division, we found that most respondents preferred divisions based on labor contribution. They also accurately guessed that others shared this preference and would approve of such divisions. Nonetheless, they still followed the prevailing norm of dividing by household. Their self-reported explanation for this behavior was that they desired to follow their traditional practices. Such a normative decision-making algorithm can allow individually consequential norms to persist without costly policing by other group members.